Resistensi Bakteri Aeromonas sp. Isolat Ikan Piranha (Pygosentrus nattereri) Bali Safari And Marine Park terhadap Antibiotik - Herawati, Ni Made; Mahatmi, Hapsari; Besung, I Nengah Kerta (Veterinary Science and Medicine Journal, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Piranha ( Pygosentrus nattereri ) is a fish that has been conserved at Conservation Center of Bali Safari and Marine Park . In May 2012 there was a case that twelve Piranhas suffered from illness and two of them d ied without any specific clinical signs. The dead Piranhas w ere necropsied and the tissues or parts of organs were collected for microbial examination interests. Spesies specific bacterial examination was also included using M icrogen GNA TM + B-ID system test The bacterial examination found that the fishes were infected by Aeromonas hydropila and Aeromonas veronii. Further examination about antibiotic resistance tests showed that those Aeromonas spp were resistant to chloramphenicol and a combination of trimethoprim and sulphamethoxazole. It can be suggested that, next, the usage of other antibiotics is strongly recommended for the case of Piranha infected by Aeromonas spp at Bali Safari and Marine Park. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Piranha, Bacterial examination, Aeromonas sp, Antibiotic resistance